2014
DOI: 10.1371/journal.pone.0099593
|View full text |Cite|
|
Sign up to set email alerts
|

Decellularized Allogeneic Heart Valves Demonstrate Self-Regeneration Potential after a Long-Term Preclinical Evaluation

Abstract: Tissue-engineered heart valves are proposed as novel viable replacements granting longer durability and growth potential. However, they require extensive in vitro cell-conditioning in bioreactor before implantation. Here, the propensity of non-preconditioned decellularized heart valves to spontaneous in body self-regeneration was investigated in a large animal model. Decellularized porcine aortic valves were evaluated for right ventricular outflow tract (RVOT) reconstruction in Vietnamese Pigs (n = 11) with 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 35 publications
1
75
0
Order By: Relevance
“…From our previous experience [19][20][21], spontaneous tissue-guided regeneration of acellular scaffolds from native heart valves proved to be an appealing technique for a straight-forward and functional clinical application. Previous studies utilize as animal model the juvenile sheep and more recently also the elderly sheep [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…From our previous experience [19][20][21], spontaneous tissue-guided regeneration of acellular scaffolds from native heart valves proved to be an appealing technique for a straight-forward and functional clinical application. Previous studies utilize as animal model the juvenile sheep and more recently also the elderly sheep [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…AVCs from both groups were implanted in 12-month-old VPs (54.3 ± 2.5 and 69.0 ± 3.7 kg for females and males, respectively) using beating heart cardiopulmonary bypass. Surgical procedure and postoperative management were performed as previously described [19][20][21].…”
Section: Vp Chronic Implant Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…4,15 In contrast, sodium cholate-and deoxycholate-based methods are useful to achieve fully nude matrices, with high in vitro and/or in vivo repopulation potentialities. [16][17][18][19] Recently, the development of decellularized xenografts or homografts with self-regeneration potential is considered as an attractive option to obtain novel viable replacements granting longer durability and avoiding the extensive in vitro cell conditioning. Various studies have already reported in situ recellularization of decellularized xenografts and homografts in animal models highlighting variable success rate in dependence on the adopted decellularization method or used graft typology (xenograft or homograft).…”
Section: Introductionmentioning
confidence: 99%